Binomial effects of high isostatic pressure and time on the microbiological, sensory characteristics and lipid composition stability of vacuum packed dry fermented sausages "chouriço". (December 2015) - Alfaia, António; Alfaia, Cristina M.; Patarata, Luís; Fernandes, Maria J.; Fernandes, Maria H.; Elias, Miguel; Ribeiro, Maria H.; Fraqueza, Maria J.
Abstract: The effect of high pressure processing (HPP), at different combinations of pressure and time, on dry fermented sausages (DFS) was evaluated by chemical, microbiological and sensory analyses. Lipid composition and stability were also assessed. HPP (> 400 MPa and longer than 154 s) produced a reduction in spoilage microbiota, without negative effect on fermentative microbiota, that will be able to continue their role. Total fatty acids and lipid stability were not affected. Only a small effect on fatty acid (FA) composition was observed. Nutritional value of the lipid fraction was only affected by the ratio n − 6/ n − 3 FA. Treatments at 400 MPa for 154 s or 960 s resulted in DFS being detected as different from control by sensory analysis. Those differences did not depreciate the product; on the contrary it seems to improve the bright aspect of the whole sausage, the cohesion and firmness and the correctly dried aspect of slices. Industrial relevance: Dry fermented meat sausages are very popular ready-to-eat meat based products. This study assesses the effects of HPP on this much appreciated traditional products. The results showed that HPP can be successfully applied to these Mediterranean fermented products without losses of sensory and nutritional characteristics. The modelling and optimization of the HPP process applied on dry fermented sausages demonstrated in this study are an advantage to industry efficiency. The utilisation of HPP by the industry can significantly increase dry fermented meat sausage shelf life and safety, providing it an opportunity to reach the global market. Highlights: The effect of HPP on the quality of traditional dry fermented sausages was assessed. HPP was shown to be a major determinant to control Gram negative spoilage microbiota. HPP did not affect fermentative microbiota of dry fermented sausages. HPP preserves the nutritional value with only a minimal effect on the product quality and sensory properties. HPP did not alter the oxidative stability of dry fermented sausages.